GGTA1/iGb3S Double Knockout Mice: Immunological Properties and Immunogenicity Response to Xenogeneic Bone Matrix. (4th June 2020) - Shao, Anliang; Ling, You; Chen, Liang; Wei, Lina; Fan, Changfa; Lei, Dan; Xu, Liming; Wang, Chengbin
Abstract : Background . Animal tissues and tissue-derived biomaterials are widely used in the field of xenotransplantation and regenerative medicine. A potential immunogenic risk that affects the safety and effectiveness of xenografts is the presence of remnant α -Gal antigen (synthesized by GGTA1 or/and iGb3S ). GGTA1 knockout mice have been developed as a suitable model for the analysis of anti-Gal antibody-mediated immunogenicity. However, we are yet to establish whether GGTA1/iGb3S double knockout (G/i DKO) mice are sensitive to Gal antigen-positive xenoimplants. Methods . α -Gal antigen expression in the main organs of G/i DKO mice or bovine bone substitutes was detected via a standardized ELISA inhibition assay. Serum anti- α -Gal antibody titers of G/i DKO mice after immunization with rabbit red blood cells (RRBC) and implantation of raw lyophilized bone substitutes (Gal antigen content was 8.14 ± 3.17 × 10 12 / mg ) or Guanhao Biotech bone substitutes (50% decrease in Gal antigen relative to the raw material) were assessed. The evaluation of total serum antibody, inflammatory cytokine, and splenic lymphocyte subtype populations and the histological analysis of implants and thymus were performed to systematically assess the immune response caused by bovine bone substitutes and bone substitute grafts in G/i DKO mice. Results . α -Gal epitope expression was reduced by 100% in the main organs of G/i DKO mice, compared with their wild-type counterparts. Following immunization with RRBC, serum anti-Gal antibody titers of G/i DKO mice increased from 80- to 180-fold. After subcutaneous implantation of raw lyophilized bone substitutes and Guanhao Biotech bone substitutes into G/i DKO mice, specific anti- α -Gal IgG, anti- α -Gal IgM, and related inflammatory factors (IFN- γ and IL-6) were significantly increased in the raw lyophilized bone substitute group but showed limited changes in the Guanhao Biotech bone substitute group, compared with the control. Conclusion . G/i DKO mice are sensitive to Gal antigen-positive xenogeneic grafts and can be effectively utilized for evaluating the α -Gal-mediated immunogenic risk of xenogeneic grafts.